GREEN CUSTOMER VALUE AND GREEN MARKETING AS ENCOURAGING SUPPORT GREEN PURCHASE INTENTION - Hermayanti, Alma Bella; Heryana, Toni; Ramdhany, Muhammad Arief; Ansamu, Umar (Finansha: Journal of Sharia Financial Management, 2024)
This study examines the influence of Green Customer Value on Green Purchase Intention, both directly and indirectly, through Green Marketing in Indonesia. Utilizing a quantitative approach, data was collected from 95 respondents aged 18-50 via an online survey. The findings indicate that Green Customer Value significantly impacts Green Marketing, underscoring that consumers' eco-friendly values enhance the effectiveness of green marketing strategies. Furthermore, Green Marketing significantly influences Green Purchase Intention, highlighting the importance of sustainability-focused marketing strategies in driving consumer purchase intentions. However, Green Customer Value does not directly affect Green Purchase Intention. Instead, its indirect effect, mediated by Green Marketing, emphasizes the need for integrating green marketing strategies to bridge the gap between consumer values and purchasing behavior. These results contribute to the literature by elucidating the components of Green Customer Value and their impact on marketing strategies. The study offers practical insights for businesses aiming to enhance eco-friendly consumer perceptions and drive sustainable purchasing decisions.